An evaluation on the effectiveness of the new value added withholding tax system in Zimbabwe - Marere, Nyasha (Midlands State University, 2018)
The new value added withholding tax regime moved from the traditional VAT collection systems to tax deduction at source. Under the traditional VAT collection system, the registered VAT operator was the one who had the mandate of preparing the VAT schedule and remitting the whole tax amount. The new system however gave the mandate to remit some of the VAT to registered value added withholding tax agents, and that is to be remitted as a withholding tax. The value added withholding tax is expected to reduce tax noncompliance and tax evasion on VAT and thereby bolstering government revenue in the process. This study evaluated the effectiveness of the value added withholding tax with a special focus on the challenges it poses to the affected taxpayers as well as the tax authority in a bid to ascertain whether it makes a good tax. The research adopted a mainly qualitative approach and the primary data was collected using questionnaires. A sample of 35 respondents was used and a response rate of 80% was achieved. The research brought to light that the new tax regime is a very noble idea to combat tax non-compliance as well as tax evasion. However, the system is underpinned many challenges that make it fall short of it being suitable in Zimbabwe like the high administration costs for both the tax authority and the agent, the inconvenience caused by the new system to the registered value added tax agents as well as to the registered operators, the perceived inequity by the taxpayers and the lack of knowledge on the subject by the taxpayers. The research recommend ed that taxing authority (ZIMRA) should continue with the new value added withholding tax system subject to educating the taxpayers on the matter, tailor making the system to suit the Zimbabwean setup and automating the system to reduce administrative burden.